Uma contribuição ao controle de motores de indução trifásicos sem o uso de sensores mecânicos - Câmara, Helder Tavares (2007)
This work presents contributions to encoderless speed servo study using three phase induction motor. Initially, a general overview on the literature is presented about control techniques applied to encoderless speed servo using induction motors. By this study, a rotor speed estimation technique is chosen to be used during this work. Some requirements like simplicity and efficiency were considered important to define this option. A study about a robust model reference adaptive controller (RMRAC) is presented to develop an encoderless speed servo with good performance in wide speed range. By this study, some encoderless speed servos were proposed to obtain good performance in low and zero speed condition, where it is the main contribution of this work. Moreover, the used RMRAC controller compensates variations on mechanical parameters and it is not needed an accurate knowledge about the plant parameters to be project. By these techniques, some algorithms based on fcem were developed where they do not depend on harmonic injection to work efficiently, as it can be verified in the presented results. Some simulation and experimental results are presented to verify the good efficiency of the proposed controllers in a wide speed range conditions, including low and zero speed conditions.